2018
DOI: 10.1155/2018/6473851
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Status of Leptospirosis in a Tropical Caribbean Area of Colombia

Abstract: Objective To describe and analyze the clinical and epidemiological status in 28 confirmed cases of human leptospirosis at the main public hospital of Cordoba. Methods Between 2012 and 2013, we conducted an active surveillance at the main hospital of Cordoba to establish the etiologic diagnosis of the undifferentiated tropical febrile illness (UTFI) cases. UTFI is defined as a fever without an infection focus in the initial physical examination or in basic laboratory tests. Patients in acute phase were accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
3
17
1
Order By: Relevance
“…However, the majority of other studies showed minimal or no gastrointestinal presentation in leptospirosis (Abgueguen et al 2008, Svarch et al 2017, Pakoa et al 2018, Sukmark et al 2018. Only a few studies showed similar finding whereby nausea, vomiting, and abdominal pain occurred in up to 60% of patients, after fever and headache by Tique et al (2018) in Columbia and about 70% in Brazil by Daher et al (2010) after fever, jaundice, myalgia, and headache.…”
Section: Clinical Presentation Of Leptospirosismentioning
confidence: 94%
“…However, the majority of other studies showed minimal or no gastrointestinal presentation in leptospirosis (Abgueguen et al 2008, Svarch et al 2017, Pakoa et al 2018, Sukmark et al 2018. Only a few studies showed similar finding whereby nausea, vomiting, and abdominal pain occurred in up to 60% of patients, after fever and headache by Tique et al (2018) in Columbia and about 70% in Brazil by Daher et al (2010) after fever, jaundice, myalgia, and headache.…”
Section: Clinical Presentation Of Leptospirosismentioning
confidence: 94%
“…Observing these unexpected GI symptoms with leptospirosis should raise the index of suspicion among clinicians seeing acute febrile patients. As reports on the frequency of GI symptoms in leptospirosis vary [4,[21][22][23], further study is needed to better characterize the clinical manifestations of leptospirosis in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Identi cation of early clinical markers associated with prolonged hospitalization or mortality will enable clinicians to promptly start the proper treatment including antibiotic initiation, starting dialysis or even ICU admission which is expected to decreases the risk for unfavorable outcome and hopefully will result in better consequences and reducing hospitalization duration and costs [25]. It is the best of knowledge that this study is the rst large scale study to investigate the factors associated with prolonged hospitalization and mortality in Malaysian population.…”
Section: Introductionmentioning
confidence: 99%